A rare case of cranial metastasis from an initial presentation of hepatocellular carcinoma - Kalal, Chetan; Wagh, Adinath; Patel, Atif; Joshi, Harshad; Surude, Ravindra; Jain, Samit; Bhatia, Shobna; Bhatt, Chetan (International Journal of Research in Medical Sciences, 2020)
Cranial metastases from hepatocellular carcinoma (HCC) has been seldom reported. Reported herein is the case of a painless parietal bone mass as an initial presentation of HCC in a 63-year-old female patient who was subsequently diagnosed to have HCV related cirrhosis. The biopsy from cranial lesion was confirmatory of HCC on immunohistochemistry. The patient had no known history of chronic liver disease. The presented diagnosis was made through detailed history, laboratory parameters and cross sectional imaging.